Specific volatiles of tea plants determine the host preference behavior of Empoasca onukii - Chen, Feng; Huang, Peng; Wang, Jun; Wu, Wei; Lin, Yong-Wen; Hu, Jin-Feng; Liu, Xin-Gang (Frontiers in Plant Science, 2023)
Empoasca onukii is a major pest that attacks tea plants. To seek effective and sustainable methods to control the pest, it is necessary to assess its host preference among different species of tea and understand the critical factors behind this behavior. In this study, the behavioral preference of E. onukii for volatile organic compounds (VOCs) of three potted tea species was evaluated. The VOCs released by the three tea species were analyzed using gas chromatography-mass spectrometry, and the major components were used to test the pest’s preference. Transcriptome analysis was used to infer the key genes that affect the biosyntheses of the VOCs. The results showed that the tendency of E. onukii toward the VOCs of the three tea species was the strongest in green tea, followed by white tea, and the weakest in red tea. This behavioral preference was significantly and positively correlated with the relative levels of hexanol, linalool, and geraniol in tea volatiles. Relative hexanol was significantly and positively correlated with the expression of genes TEA009423 (LOX2.1), TEA009596 (LOX1.5), TEA008699 (HPL), TEA018669 (CYPADH), and TEA015686 (ADHIII). Relative linalool was significantly and positively correlated with the expression of genes TEA001435 (CAD) and Camellia_sinensis_newGene_22126 (TPS). Relative geraniol was significantly and positively correlated with the expression of genes TEA001435 (CAD), TEA002658 (CYP76B6), TEA025455 (CYP76T24), and Camellia_sinensis_newGene_22126 (TPS). The above findings suggested that three volatiles (hexanol, linalool, and geraniol) determined the behavioral preference of E. onukii toward tea plants, and their biosynthesis was mainly affected by nine genes (TEA009423, TEA009596, TEA008699, TEA018669, TEA015686, TEA001435, TEA002658, TEA025455, and Camellia_sinensis_newGene_22126).